ANALYSIS OF PICKLE PACKAGING EQUIPMENT - Witt, Christopher (Kansas State University, 2016)
Best Maid is a middle-sized regionally orientated company, headquartered in Fort Worth, Texas. It is currently owned and operated by the fourth generation of the Dalton family. The company specializes in the production of pickles and condiment products and currently holds the title of #1 retail brand of pickles in the state of Texas. In addition to the Best Maid label, products are also produced under the Del-Dixie label. The objective of this thesis is to analyze a potential capital project: a bucket line replacement. The analysis will be completed by using net present value to determine the cost and benefits of the project. The focus of the project will be the food service bucket line. The current line was designed and installed over 20 years ago. Currently, this line and supporting resources require a staff of 17 employees to operate. The process is looking to be improved through advances in technology including vibratory conveyors, more complex PLC programming, and increased accuracy of scaling equipment. Implementing these advancements has the potential to reduce the employee labor cost as well as decrease over-scaling. The goal of this project is to inform the Best Maid owners of the investment costs, labor savings, benefits, and the financial viability of the proposed capital investment. Best Maid has consistently grown at a high single digit to low double digit rate each year. Businesses must continually identify and react to the needs of tomorrow, today. Formal processes within the business will be established to evaluate and prioritize future potential projects. The conclusion of the analysis resulted in a positive NPV of about $567 thousand and a favorable IRR. The recommendation is to adopt the new technology.
Keywords: Pickle packaging; Investment analysis; Net present value; Technology adoption